DAYA PATOGENESITAS Helicoverpa armigera Nuclear Polyhedrosis Virus HaNPV SETELAH TERKENA RADIASI SINAR ULTRAVIOLET - Mahanani Tri Asri; Isnawati Isnawati (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2000)
This research is about pathogen capacity of the Helicoverpa armigera nuclear Polyhedrosis Virus (HaNPV) after irradiation by ultra violet (UV) light. The HaNPV is the one kind of the virus which attack the insect Helicoverpa armigera-attacker the some species of the crop life tobacco, cotton, potato, tomato. Because of that the HaNPV can be used as the biological control of the pest. Some researcher stated that the pathogen capacity of the HaNPV is decrease if the virus was expose in the ultra violet (UV) light. Because of the fact the virus in not useful as the biological control of the pest in the land corp. This research to test the statement. Laboratory experimental was done to tested the pathogen capacity of the HaNPV after irradiation treatment by the ultra violet light. The intensity of the UV light in this experiment were 28.7 lux, 97.3 lux, and 127.4 lux with the lighting period were 0, 1, 3, 6, 9, 12, and 15. The result of the research stated that the pathogen capacity of the HaNPV was not influenced by ultra violet light. So the virus is still useful as the biological control of the pest in the land crop.